Inpit Crushing Convey (IPCC) for Overburden as Option for Optimizing Mine Operational in PT. Kaltim Prima Coal (The Indonesian Journal of Business Administration, 2015)
Abstract. Since 2012, coal price was decreased dramatically and it has impacted globally. The derivation of coal price also has multiplier effect to internal business process KPC. KPC must have strategies to survive and sustain. According to those challenges, KPC must find a way to reduce cost and optimize profit margin start from mine operation activity until shipping activity. One of the ways is to reduce operational cost such as using fuel efficiency for overburden truck. The challenge facing are KPC trucks are old and dump location of overburden is too far from mining area. So as to meet the production targets required a considerable amount of trucks and need a lot of fuel.One way to save on production costs is by using the IPCC system (Inpit Crushing Convey). This system has a low production costs partly because of the use of fuel that is not as wasteful as OB truck. But on the other hand, these systems require huge capital for the purchase of this new semi-fixed equipment, while the extension of coal contract of work of KPC beyond the year 2021 there is no certainty. If KPC was not extended beyond 2021, this equipment only less than 7 years old and after the year 2021 that equipment will be owned by the state.In this research, there are 3 projects are compared to find the most inexpensive production costs. Three projects are re-built the truck, using the IPCC system, and using existing truck. The analysis has used the NPV analysis and theory of probability. In analysis using theory of probability, the conditions of project are presented on 2 conditions related to the extension of the mining permit on beyond year of 2021 is unclear. The first condition, the Coal Contract of Work (CCoW) of KPC is extended and second condition, CCoW of KPC is not extended. Because there is an uncertainty for extension of CCoW of KPC, then the value of the probability for the extended conditions (continued) was 0.67 and the conditions CCoW of KPC not extended (stop) is 0.33. For selection of the placement location IPCC system is using the method of Simple Multi-Attribute Rating Technique or in abbreviation SMART Analysis. With consider various factors, the ideal location is in pit Bendili with dumping area is AB void. That location has the highest aggregate value from the 5 other locations. From the results obtained, although the actual calculation for the use of the IPCC system had expected the greatest value among the two other project, for the condition of the existing truck, has the lowest risk if KPC is not extended, because it has not expended a capital investment.Keywords: SMART Analysis, Theory of Probability, Uncertainty Condition of Permit Extend, Capital and Production Cost, Equipment Selection.